2019
DOI: 10.1038/s41598-019-54021-4
|View full text |Cite
|
Sign up to set email alerts
|

Eurotium Cristatum Fermented Okara as a Potential Food Ingredient to Combat Diabetes

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic disease, and dietary modification is a crucial part of disease management. Okara is a sustainable source of fibre-rich food. Most of the valorization research on okara focused more on the physical attributes instead of the possible health attributes. The fermentation of okara using microbes originated from food source, such as tea, sake, sufu and yoghurt, were explored here. The aim of this study is to investigate fermented okara as a functional food ingredient to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 32 publications
(29 reference statements)
2
21
0
1
Order By: Relevance
“…Furthermore, metabolomics contributes to a better understanding of the biotransformation of bioactive compounds [158]. As a substrate for microorganisms, okara has been widely used in different fermented modes [159][160][161][162][163][164]. Rhizopus oligosporus, Bacillus subtilis WX-17, and Eurotium cristatum were used for okara fermentation, resulting in products with higher bioactivity, nutritional composition, and anti-diabetic potential [159][160][161][162][163][164].…”
Section: Bioactive Compounds In Industrial By-products From Soybean Processing-an Overview and Trendsmentioning
confidence: 99%
“…Furthermore, metabolomics contributes to a better understanding of the biotransformation of bioactive compounds [158]. As a substrate for microorganisms, okara has been widely used in different fermented modes [159][160][161][162][163][164]. Rhizopus oligosporus, Bacillus subtilis WX-17, and Eurotium cristatum were used for okara fermentation, resulting in products with higher bioactivity, nutritional composition, and anti-diabetic potential [159][160][161][162][163][164].…”
Section: Bioactive Compounds In Industrial By-products From Soybean Processing-an Overview and Trendsmentioning
confidence: 99%
“…Similarly, an increase in protein content was observed after fermentation, which is consistent with the current findings. Chan et al (2019) reported that the fermentation of okara using E. cristatum after 10 days resulted in an increase in protein content from 22.3% to 32.6% [ 16 ]. According to Sitanggang et al (2019), the fermentation of okara using A. oryzae resulted in an increase in protein content from 24.0% to 41.1% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the few studies that have been carried out prove its considerable potential as a functional food ingredient. In a previous study, okara fermented with Eurotium cristatum showed an antidiabetic potential with a potent α-glucosidase and PTP1B inhibitory activity [ 16 ]. Additionally, okara fermented with A. oryzae can also attenuate the progression of type 2 diabetes by reducing insulin resistance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, when okara treated with Eurotium cristatum, a type of fungus used in the production of Chinese tea, was mixed in the diet at a ratio of 20% and fed to type 2 diabetic mice, the high blood glucose levels were reduced to levels that allowed normal eating. This diet is sufficient in calories (348 kcal), well-balanced in dietary fibre (5.5 g/100 g) and protein (6.6 g/100 g), and low in fat (2.5 g/100 g) [110]. Additionally, the fermentation of okara by the Lactobacillus acidophilus, Lacticaseibacillus rhamnosus, and Pediococcus acidilactici species gives it a buttery taste and enhances its value as a food.…”
Section: Ammonia Production By Metabolic and Cell Engineeringmentioning
confidence: 99%